Power sharing and management in a utility connected DC microgrid - Datta, A.; Ghosh, Arindam; Rajakaruna, Sumedha (IEEE, 2018)
© 2017 IEEE. This paper introduces a control technique for proportional load sharing in a DC microgrid during both islanded and utility connected modes. The DC microgrid is connected to a utility system through an interlinking voltage source converter and a unidirectional DC-DC converter. The DC-DC converter draws the desired amount of power from the utility, while the interlinking converter holds the DC bus voltage. The DERs in the DC microgrid are operated under droop sharing using DC-DC converters. Each DC-DC converter is equipped with a state feedback with integral controller that can regulate its output voltage for a wide range of input voltage fluctuation and load variation. Simulation studies are conducted on PSCAD/EMTDC to validate the proposal.